Analisis Pengaruh Upah Minimum, Inflasi, dan Tenaga Kerja Formal terhadap Produk Domestik Regional Bruto: Studi Panel Data Provinsi di Indonesia (2018-2024) - Jennifer Joan Pingkan (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study examines the impact of minimum wage, inflation, and formal employment on Regional GDP in Indonesia using panel data from 34 provinces (2018-2024). Fixed effects model results show: (1) an 1% increase in minimum wage raises GDP by 1.48% (p<0.001); (2) inflation has a positive 0.018% effect; (3) a 1% increase in formal employment boosts GDP by 0.019%. These findings confirm the importance of appropriate wage policies, inflation control, and labor formalization for regional economic growth.